INTEGRATED METHODS FOR PERFORMANCE MEASUREMENT IN ENTITIES FROM THE WINE SECTOR IN ROMANIA - BRICIU, Sorin; TOPOR, Dan Ioan; CĂPUȘNEANU, Sorinel (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 15 (2013): Annales Universitatis Apulensis Series Oeconomica, 2013)
This article highlights the authors attempt to identify modern cost calculation methods and appropriate performance measurement tools and their integration in order to improve the performance of the economic entities from the wine sector in Romania. Identifying methods and tools for performance measurement are based on an analysis of a representative sample of specialists from the economic entities from wine sector in Romania. The article is littered with empirical studies designed to highlight the performance of the economic entities from the wine sector based on using the integrated methods such as Activity Based Costing (ABC) method and Balance Scorecard (BS) method. All the results obtained based on the specific methodology of the methods studied are analyzed by the authors. The article ends with the conclusions of the authors on using integrated methods for measuring performance in the entities from the wine sector in Romania.